PENINGKATAN AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN TEMATIK MENGGUNAKAN PENDEKATAN VCT MODEL MATRIKS DI SDN 36 CENGKEH KOTA PADANG - Satria Efendi; Reinita Reinita (Universitas Negeri Padang, 2019)
In order to enhance the students' learning activities on thematic learning at SDN 36 Cengkeh, Padang. Classroom action research conducted. Objectives to be achieved by the researchers is to increase the activity of teachers and students during the learning takes place by using the Matrix Model VCT approach. This study consisted of two cycles with data analysis techniques qualitative and quantitative descriptive implemented through three stages: planning, action and observation, reflection. The data collection was assisted by VB classroom teachers using teacher and student activity sheets. The results showed that the activity of teachers increased by 6% from 78% in the first cycle to 84% in the second cycle. While the student activity increased by 9% from 75% in the first cycle to 84% in the second cycle.